A relação da memória de trabalho e da memória de longo prazo no processamento de itens referenciais na leitura de textos escritos - Rocha, Patrícia de Brito (2007)
This research tried to verify whether there are cognitive relationships among the processing of referential mechanisms, working memory and long term memory while readers grapple with texts. In a first moment, the investigation aimed at discovering whether students who are about to end their junior high school would be able or not be able to carry out the processing of the referential mechanisms in personal and demonstrative referencing while reading written texts; in a second moment, the work tried to verify whether the same students, when exposed to the re-occurrence of the text, would accomplish a better performance, presenting relationship or not between the working memory and the long term memory. To accomplish that, we chose an experimental research. In order to attain the data, we specified distinct phases to be accomplished , such as: in the first phase, we tried to put together the reading proficiency of the students, based on an informative questionnaire; at this phase, we aimed to separate them into two distinct groups: an intervention group and a control group; then , the students who belonged to the first group were brought into the intervention process in which the notions of reference and its relevance for the production and comprehension of the text were explained, while the students who belonged to the control group did not have such instructions. After the intervention process, both groups did two tests in order to verify the effects in the long term memory. Based on the results, figures and analyses of the data we have obtained with the pre-tests, we realized that the intervention group shown in both tests a performance that is significantly higher than the one of the control group; in addition, the control group, although having shown a lower performance in relation to the intervention group, reached a better performance in the second test rather than in the first one; this fact indicates that the re-occurring of texts could improve the performance in reading activities. According to these results, we observed that the initial hypothesis that the working memory and the long term memory are related in the processing of referential items and that the re occurring of texts could improve the performance of the readers when reading written texts were confirmed. This way, it is possible to state that the teaching process of reading should focus on the consolidation of memories through the re-occurring of texts and not only with mere decoding.